In vitro percutaneous penetration and characterization of silver from silver-containing textiles - Bianco C (Dove Medical Press, 2015)
Carlotta Bianco,1 Sanja Kezic,2 Matteo Crosera,1 Vesna Svetličić,3 Suzana Šegota,3 Giovanni Maina,4 Canzio Romano,5 Francesca Larese,6,7 Gianpiero Adami11Department of Chemical and Pharmaceutical Sciences, University of Trieste, Trieste, Italy; 2Academic Medical Center, Coronel Institute, University of Amsterdam, Amsterdam, the Netherlands; 3Laboratory for Bioelectrochemistry and Surface Imaging, Division for Marine and Environmental Research, Ruder Boškovic Institute, Zagreb, Croatia; 4Department of Clinical and Biological Sciences, University of Turin, Turin, Italy; 5Department of Public and Pediatric Health Sciences, University of Turin, Turin, Italy; 6Unit of Occupational Medicine, University of Trieste, Trieste, Italy; 7Department of Medical Sciences, University of Trieste, Trieste, ItalyAbstract: The objective of this study was to determine the in vitro percutaneous penetration of silver and characterize the silver species released from textiles in different layers of full thickness human skin. For this purpose, two different wound dressings and a garment soaked in artificial sweat were placed in the donor compartments of Franz cells for 24 hours. The concentration of silver in the donor phase and in the skin was determined by an electrothermal atomic absorption spectrometer (ET-AAS) and by inductively coupled plasma mass spectrometer (ICP-MS). The characterization of silver species in the textiles and in the skin layers was made by scanning electron microscopy with integrated energy dispersive X-ray spectroscopy (SEM-EDX). Additionally, the size distribution of silver nanoparticles in the textiles was performed by atomic force microscopy (AFM). On the surface of all investigated materials, silver nanoparticles of different size and morphology were found. Released silver concentrations in the soaking solutions (ie, exposure concentration) ranged from 0.7 to 4.7 µg/mL (0.6–4.0 µg/cm2), fitting the bactericidal range. Silver and silver chloride aggregates at sizes of up to 1 µm were identified both in the epidermis and dermis. The large size of these particles suggests that the aggregation occurred in the skin. The formation of these aggregates likely slowed down the systemic absorption of silver. Conversely, these aggregates may form a reservoir enabling prolonged release of silver ions, which might lead to local effects.Keywords: silver textile, silver release, skin